Perhitungan Kerugian Keuangan Negara Dalam Tindak Pidana Kasus Korupsi - Intan Timur (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2021)
This research aims to disclose the understanding regarding the calculation on the state financial losses arising on the corruption crime. The type of this research was qualitative using discourse analysis through Norman Fairclough model. In the legal understanding, the calculation of total loss must be in accordance with the fact how much the cost has been recovered or has been paid by the defendant is not counted as state losses. While in the auditor's calculation method, the total loss is the total of all funds issued by the state, thus the money is recognized as state losses.